2023
DOI: 10.1155/2023/1064955
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical-Epidemiological Study on Beta-Blocker Poisonings Based on the Type of Drug Overdose

Abstract: Background. Beta‐blockers carry a high risk of potentially causing fatal poisoning if overdosed. We aimed to assess the clinical and epidemiological characteristics of patients with beta-blocker poisoning. Methods. Patients were categorized based on the type of drug poisoning into propranolol, other beta-blockers, and the combination of beta-blocker groups, respectively. Demographic data, drug toxicity, and clinical, laboratory, and treatment information of different groups were compared. Results. During the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…19 In a study of beta-blocker poisoning in people in an Iranian hospital, 84.4% of the 255 poisonings involved propranolol alone or in combination. 23 A Finnish study compared propranolol and metoprolol at post-mortem between 2016–2018. 24 Although metoprolol ( n = 416) was detected in more cases than propranolol ( n = 179), deaths involving propranolol were more often intentional self-poisoning, and benzodiazepines, antidepressants and antipsychotics were more often co-detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In a study of beta-blocker poisoning in people in an Iranian hospital, 84.4% of the 255 poisonings involved propranolol alone or in combination. 23 A Finnish study compared propranolol and metoprolol at post-mortem between 2016–2018. 24 Although metoprolol ( n = 416) was detected in more cases than propranolol ( n = 179), deaths involving propranolol were more often intentional self-poisoning, and benzodiazepines, antidepressants and antipsychotics were more often co-detected.…”
Section: Discussionmentioning
confidence: 99%
“…2 According to open-access UK prescribing data, almost 600 000 prescriptions of propranolol are dispensed monthly. 3 The prevalence of propranolol prescribed for patients with anxiety recorded in general practice more than doubled from 3.8/1000 person-years at risk in 2008 to 8.7/1000 person-years at risk in 2018, and the most substantial increase in prescribing was in young adults (age [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. 4 Reasons for this rise could include: general practitioners (GPs) prescribing propranolol more readily than other medications as they describe propranolol as non-addictive; 5 a reduction in incident benzodiazepine prescribing in alignment with national guidance; 4 and GPs wanting to 'do something' while waiting for referral to psychological therapies, as has been reported for antidepressant prescribing in depression.…”
mentioning
confidence: 99%
“…Around 8761 (79.7%) of these exposures were unintentional [ 1 ]. From a retrospective study involving 5086 hospitalized poisoned patients, beta-blocker poisoning was identified in 5.1% of cases, and propranolol toxicity was the predominant presentation, accounting for 84.4% of beta-blocker poisonings [ 2 ].…”
Section: Introductionmentioning
confidence: 99%